Moderating Role of Organizational Justice between Emotional Exhaustion and Job-related Outcomes: Longitudinal Study at Education Sector - Shahid, Ayesha; Nisar, Qasim Ali; Azeem, Muhammad; Ul Hameed, Waseem; Hussain, Sajjad (2017)
Previous studies anticipated that there is need of justice in educational institutions in order to protect the academicians’ psychological as well as emotional needs under teaching profession. Therefore, the purpose of current study is to examine the moderating role of organizational justice between the relationship of emotional exhaustion and job related outcomes (Organizational commitment and Organizational loyalty).In order to accomplish this purpose, the survey questionnaire method was used. The study is quantitative, descriptive and longitudinal in nature. 250 respondents were selected in time1 & time2 by applying simple random sampling. Results indicated that emotional exhaustion and employee loyalty are negatively associated with each other (Bt1= -.328; Tr2= -.329). Similarly negative correlation found between emotional exhaustion and commitment (Tr1= -.425; Tr2= -.427).Results in time2 exhibited more understanding about understudy relationships. Moreover, results also enlightened that organizational justice significantly moderate on the relationship of emotional exhaustion and job related outcomes (Organizational commitment and Organizational loyalty).